Revisiting Epithelial Carcinogenesis - Méndez López, Luis Fernando (Molecular Diversity Preservation International, 2022)
The origin of cancer remains one of the most important enigmas in modern biology. This paper presents a hypothesis for the origin of carcinomas in which cellular aging and inflammation enable the recovery of cellular plasticity, which may ultimately result in cancer. The hypothesis describes carcinogenesis as the result of the dedifferentiation undergone by epithelial cells in hyperplasia due to replicative senescence towards a mesenchymal cell state with potentially cancerous behavior. In support of this hypothesis, the molecular, cellular, and histopathological evidence was critically reviewed and reinterpreted when necessary to postulate a plausible generic series of mechanisms for the origin and progression of carcinomas. In addition, the implications of this theoretical framework for the current strategies of cancer treatment are discussed considering recent evidence of the molecular events underlying the epigenetic switches involved in the resistance of breast carcinomas. The hypothesis also proposes an epigenetic landscape for their progression and a potential mechanism for restraining the degree of dedifferentiation and malignant behavior. In addition, the manuscript revisits the gradual degeneration of the nonalcoholic fatty liver disease to propose an integrative generalized mechanistic explanation for the involution and carcinogenesis of tissues associated with aging. The presented hypothesis might serve to understand and structure new findings into a more encompassing view of the genesis of degenerative diseases and may inspire novel approaches for their study and therapy